Expression levels of FGFR3 as a prognostic marker for the progression of primary pT1 bladder cancer and its association with mutation status - Kang, Ho Won (Oncol Lett, 2017)
The present study examined the utility of fibroblast growth factor receptor 3 (FGFR3) mutation status and gene expression as a prognostic marker in primary pT1 bladder cancer (BC). A total of 120 patients with primary pT1 BC were enrolled. FGFR3 mutation status was determined by direct sequencing and FGFR3 mRNA expression level was determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis. The results were compared with the clinicopathological parameters, and the prognostic value of FGFR3 was evaluated by Kaplan-Meier analysis and a multivariate Cox regression test. FGFR3 mutations were identified in 48/120 (40.0%) patients with pT1 BC. FGFR3 mRNA expression level was significantly higher in those with BC harboring FGFR3 mutations (P<0.001). Low FGFR3 expression level was associated with high-grade tumors and cancer progression (P=0.006 and P=0.001), whereas FGFR3 mutation status was not associated with cancer progression. Kaplan-Meier analysis revealed a similar result (log-rank, P<0.001). Multivariate analysis identified low FGFR3 expression level (odds ratio, 3.300; 95% confidence interval, 1.310–8.313; P=0.011) as an independent predictor of cancer progression. Stratification by exon site of FGFR3 mutations yielded significant differences in mRNA expression level. None of the patients with BC harboring FGFR3 mutations in exon 9 demonstrated disease progression. The mRNA expression level of the FGFR3 gene may be used to precisely identify subsets of patients with pT1 BC that have a relatively better prognosis. The prognostic influences of FGFR3 mutations may be modulated by the exon site of FGFR3 mutations.